Pengaruh Penambahan Gelatin terhadap Karakteristik Marshmallow Bunga Telang (Clitoria Ternatea L.) - Sorena, Tanita Abigail; Wisaniyasa, Ni Wayan; Putra, I Gede Arie Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPA, 2024)
This study aimed to determine the effect of gelatin addition on the characteristics of butterfly pea marshmallows, as well as to determine the right addition of gelatin to produced butterfly pea marshmallows with the best characteristics. The experimental design used in this study was a completely randomized design with gelatin addition treatments consisting 5 levels (4 percent, 5 percent, 6 percent, 7 percent, and 8 percent) of the total ingredients. All treatments were repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by analysis of variance and if the treatment had the significance effect to the observation variables, then continued with Duncan's Multiple Range Test. The observed variables included water content, ash content, antioxidant activity, total anthocyanins, hedonic (color, aroma, taste, texture and overall acceptance) and scoring (texture). The results showed the addition of 7 percent gelatin produced butterfly pea marshmallows with the best characteristics, such as water content of 23.35 percent, ash content of 0.089 percent, antioxidant activity of 56.68 percent, total anthocyanins 0.0406mg/100g, color (slightly liked), aroma (neutral), taste (liked), texture (liked) with chewy texture scoring test criteria, and overall acceptance was liked. Keywords: marshmallow, gelatin, butterfly pea